Cultural and biological factors modulate spatial biases over development. Issue 6 (2nd November 2017) - Girelli, Luisa; Marinelli, Chiara Valeria; Grossi, Giuseppe; Arduino, Lisa S.
ABSTRACT: Increasing evidence supports the contribution of both biological and cultural factors to visuospatial processing. The present study adds to the literature by exploring the interplay of perceptual and linguistic mechanisms in determining visuospatial asymmetries in adults (Experiment 1) and children (Experiment 2). In particular, pre-schoolers (3 and 5 year-olds), school-aged children (8 year-old), and adult participants were required to bisect different types of stimuli, that is, lines, words, and figure strings. In accordance with the literature, results yielded a leftward bias for lines and words and a rightward bias for figure strings, in adult participants. More critically, different biases were found for lines, words, and figure strings in children as a function of age, reflecting the impact of both cultural and biological factors on the processing of different visuospatial materials. Specifically, an adult-like pattern of results emerged only in the older group of children (8 year-old), but not in pre-schoolers. Results are discussed in terms of literacy, reading habits exposure, and biological maturation.